Weizmannia coagulans BC99 modulate gut microbiota after Helicobacter pylori eradication: A randomized double-blind placebo-controlled trial - Ying Wu; Shirui Zhai; Caie Wang; Zhouya Bai; Pingping Tian; Shanshan Tie; Yao Wang; Yingjian Zhang; Lina Zhao; Shaobin Gu (Journal of Functional Foods)
Probiotics interventions may contribute to eradicate Helicobacter pylori infection and reduce gastrointestinal symptom, but their mechanisms require more research. This study involved 100H. pylori-positive adults, randomly assigned to either Weizmannia coagulans BC99 group or Placebo group. Both groups were received bismuth quadruple therapy for 4 weeks and took either BC99 or placebo for 6 weeks. After 6 weeks, BC99 significantly reduced eradication rate and happening of adverse events. BC99 reduced GSRS score, particularly the severity of stomach-abdominal pain during hunger symptoms. Additionally, BC99 reduced the disruption of bismuth quadruple therapy on the gut microbiota, particularly significantly increasing the abundance of Prevotella, Bacillus, Candidatus_Saccharimonas and reducing the abundance of Lachnoclostridium, Intestinibacter, Holdemania, Desulfovibrio. These findings supported the use of W. coagulans BC99 in combination with BQT in the clinical management of patients with H. pylori infection.